THE RELATIONSHIP BETWEEN ROLE OF THE FAMILY WITH LEVEL OF DEPRESSION IN ELDERLY - Ali Sairozi; Cherlys Tin Lutfiandini; Endah sri Wijayanti; Iswatun Iswatun (Journal of Vocational Nursing, 2023)
Introduction: Depression is a Introduction: Depression is an emotional disorder in the form of feeling depressed, unhappy, worthless and lack of enthusiasm in life. Elderly people are vulnerable to depression because of their low health status, loss of a partner due to death, and the low level of social support they receive. The family has an important role for the elderly in developing, preventing and overcoming health problems. This study aims to determine the relationship between the role of the family and the level of depression in the elderly in Sungegeneng Village, Sekaran District, Lamongan Regency. Methods: the research used a cross-sectional design, the samples in this study were elderly people and families who lived at home with elderly people in Sungegeneng Village, Sekaran District, Lamongan Regency who met the inclusion criteria with a sample size of 39 people. Spearman rho correlation testing was carried out using SPSS. Results: The results of the Spearman test and data analysis using the SPSS 11.5 for Windows program between the role of the family and the level of depression in the elderly in Sungegeneng Village, Sekaran District, Lamongan Regency, obtained a result of Ï = 0.000 with a significance level of α = 0.01, so H0 is rejected, meaning there is a significant relationship Between the role of the family and the level of depression in the elderly. Conclusions: There is a relationship between the role of the family and the level of depression in the elderly in Sungegeneng Village, Sekaran District, Lamongan Regency.